PENGEMBANGAN DESAIN PEMBELAJARAN KREATIF-PRODUKTIF DALAM PEMBELAJARAN BIOLOGI TERHADAP PENCAPAIAN AKTIVITAS KOGNITIF SISWA SMA DI KABUPATEN BANYUMAS - Teguh Julianto; Arif Husin (Khazanah Pendidikan, 2018)
Research on the development of creative-productive learning designs inbiology learning on the achievement of cognitive activities of high schoolstudents in Banyumas Regency has been carried out using the experimentalmethod. Schools that are the sample of the study are based on the results of therandom (draw) there are 4 schools from 15 schools in Banyumas Regency. Datacollection techniques were carried out through observation to observe students'cognitive activities and tests (pretest and posttest) to obtain learning outcomesdata. Cognitive activity observed in the form of activity observing objects,identifying activities; activity explains; connecting activities; classifyingactivities; and activities to communicate data. Data analysis was conducted inqualitative and quantitative descriptive ways to get a comprehensive picture ofthe research activities. The results of the analysis of the data obtained from theseactivities show that the Creative-Productive learning model has a positive effecton the achievement of cognitive activities of students in biology learning. Theconclusion of this study is that the development of Creative-Productive learningdesign in biology learning has a positive effect on the achievement of cognitiveactivities of high school students in Banyumas Regency.Keywords: learning design, creative-productive, cognitive activity, learningoutcomes